Dynamics of Surface Deformation Induced by Dikes and Cone Sheets in a Cohesive Coulomb Brittle Crust. Issue 10 (21st October 2017) - Guldstrand, F.; Burchardt, S.; Hallot, E.; Galland, O.
Abstract: The analysis of surface deformation associated with intruding magma has become an established method to study subsurface processes and intrusion architecture. Active subsurface magmatism induces deformation that is commonly modeled using static elastic models. To what extent, Coulomb failure of the crust affects surface deformation remains, so far, largely unexplored. In this contribution we present quantitative laboratory results of surface deformation induced by the emplacement of simulated dikes and cone sheets in a cohesive Coulomb material. The analysis of the experimental surface deformation shows that these intrusion types produce distinct and characteristic surface deformation signatures, which reflect the evolution of the intrusion at depth. Generally, dikes show a two‐phase evolution while cone sheets develop gradually. In comparison, cone sheets induce larger uplifted areas and volumes than dikes relative to the depth of the injection source. Dike formation is, in turn, is likely accommodated, to a larger degree than cone sheets, by lateral opening of the host consistent with our current understanding of dike emplacement mechanics. Notably, only surface uplifts develop above the experimental dikes, consistent with a viscous indenter propagation mechanism, that is, a dike pushing ahead. The measured surface deformation patterns associated with dikes starkly contrast with established static, elastic models that predict local subsidence above the tip of a dike. This suggests that Coulomb failure of crustal rocks may considerably affect surface deformation induced by propagating igneous intrusions. This is especially relevant when a relatively high viscosity magma intrudes a weak host, such as unconsolidated sedimentary and volcaniclastic rocks. Key Points: Laboratory models of surface deformation associated with dike and cone sheet emplacement in a cohesive Coulomb crust Dike emplacement systematically triggers surface uplift, in contrast to established elastic models We identify distinct surface deformation patterns and evolutions associated with dike and cone sheet emplacement